2019
DOI: 10.1017/dmp.2018.170
|View full text |Cite
|
Sign up to set email alerts
|

Response to a Fire Incident in the Operation Room: A Cautionary Tale

Abstract: Health care facilities are always seen as places of haven and protection for managing external incidents, but situations become difficult and challenging when such facilities themselves are affected by internal hazards. Such incidents are arguably more disruptive than external incidents, because patients are dependent on supportive measures and are neither in position to respond to such crisis situation nor do they know how to respond. Operating room fires are rare but potentially catastrophic, involving loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…A case study about a fire in an operation room in India found that holding fire drills could improve hospitals' response to fire, minimize the incidence of potentially fatal problems, and create a more secure environment for patients and personnel. [ 81 ] Other studies have also emphasized on educating personnel about fire safety plans, firefighting, evacuation of patients based on triage, and identification of vulnerable patients to boost. The knowledge and performance of hospital personnel in managing fire and ensure patients' and staff's safety.…”
Section: Search Resultsmentioning
confidence: 99%
“…A case study about a fire in an operation room in India found that holding fire drills could improve hospitals' response to fire, minimize the incidence of potentially fatal problems, and create a more secure environment for patients and personnel. [ 81 ] Other studies have also emphasized on educating personnel about fire safety plans, firefighting, evacuation of patients based on triage, and identification of vulnerable patients to boost. The knowledge and performance of hospital personnel in managing fire and ensure patients' and staff's safety.…”
Section: Search Resultsmentioning
confidence: 99%
“…In healthcare settings, the origin for a majority of these fire incidents has been electricity linked causes, specifically along the bed-head side of the patient care areas, as these areas have rich oxygen density, equipment complexity, web of cables, abundance usage of highly inflammable chemicals, and hand sanitizers. [ 3 4 5 6 7 ] Generally, a bed-head panel consists of modular sections (usually 4–14 numbers), for electrical supply to run monitors, ventilators, and defibrillators along with points for illumination, communication, and medical gases, liquids, and anesthetic gas scavenging systems. Though these bed-head units operate reliably and safely, yet leakage from these gases' outlets cannot be ruled out completely.…”
Section: Introductionmentioning
confidence: 99%
“…IHCDs have the potential to threaten the wellbeing of patients and staff (injured persons, casualties) and may cause catastrophic damage and/ or total loss of function despite the institution's full resource mobilization [3][4][5]. Globally, internal hospital disasters seem to occur with regularity; reported causes include natural disasters [6,7], toxic substances [8], structural failures [9], fires [10,11], flooding [12] and terrorist threats [13].…”
Section: Introductionmentioning
confidence: 99%